Panduan Aplikatif Rancangan Bangun Elemen Mesin dengan AutoDesk : Mechanical Deksktop 6.0 - [Tidak Terdaftar] (Andi Offset, 2003)
Panduan Aplikatif Rancangan Bangun Elemen Mesin dengan AutoDesk : Mechanical Deksktop 6.0